GEOPHYSICAL METHODS APPLICATION AT THE INVESTIGATION OF HYDROTECHNICAL TUNNELS TRACES IN MOUNTAIN-FOLDED AREAS (Proceedings of the YSU C: Geological and Geographical Sciences, 2017)
In the article multiple examples of geophysical investigations in mountainfolded areas for hydrotechnical tunnel constructing are analyzed. Mountain-folded areas have difficult structure and for investigations is required a special complex of geophysical methods.
Keywords: hydrotechnical tunnel; geophysical method; mountain-folder area